Pengaruh pendapatan dan pendidikan terhadap tingkat fertilitas di Provinsi Gorontalo - Ilyas Idris, Zulkarnain (Jurnal Paradigma Ekonomika, 2022)
In Gorontalo Province, the population from year to year has increased where from 2015 to 2019 it increased but in 2018 it had decreased. This research is of course to find out the cause of the fertility rate in Gorontalo Province as seen from the income and education of the people in 6 Regencies/Cities throughout Gorontalo Province from 2015-2019. The data sources used in this study are secondary data from the Central Statistics Agency and the Gorontalo Provincial Health Office. The analytical method used is panel data, which is a combination of cross section and times series using the Random Effect Model approach. The results showed that income had a positive and significant effect on fertility levels and education had no effect on fertility levels in Gorontalo Province.